2012
DOI: 10.2337/dc11-0537
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Among an Urban Population in Kenya

Abstract: OBJECTIVEDeveloping countries are undergoing an epidemiologic transition accompanied by increasing burden of cardiovascular disease (CVD) linked to urbanization and lifestyle modifications. Metabolic syndrome is a cluster of CVD risk factors whose extent in Kenya remains unknown. The aim of this study was to determine the prevalence of metabolic syndrome and factors associated with its occurrence among an urban population in Kenya.RESEARCH DESIGN AND METHODSThis was a household cross-sectional survey comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
59
4
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 21 publications
22
59
4
4
Order By: Relevance
“…11 The higher prevalence in women than men has also been reported in several SSA countries [12][13][14]16 as well as in African-Americans. 17 However, nonAfrican-Americans 17 and other developed nations do not demonstrate a clear trend for metabolic syndrome between the sexes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…11 The higher prevalence in women than men has also been reported in several SSA countries [12][13][14]16 as well as in African-Americans. 17 However, nonAfrican-Americans 17 and other developed nations do not demonstrate a clear trend for metabolic syndrome between the sexes.…”
Section: Discussionmentioning
confidence: 87%
“…17 However, nonAfrican-Americans 17 and other developed nations do not demonstrate a clear trend for metabolic syndrome between the sexes. 12,17,18 The reason for the clear sex differences in metabolic syndrome rates in SSA and African-Americans may be related to cultural values and positive social attitudes toward fatness, 13 which contribute to the markedly higher obesity levels in women than men as found in this study (86.0% vs. 20.1%). In African cultures, being overweight is accepted and even desired as it is perceived to be associated with dignity, respect, wealth, strength, attractiveness, happiness and health, and with women being well-treated by their husbands.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…54 The four related Kenyan studies that our search yielded were all done at Kenyatta National Hospital. 33,34,40,41 Our study population (Table 8) had prevalence of 4% high total cholesterol, 14% suboptimal HDL cholesterol, 4% high/very LDL cholesterol and < 4% high triglyceridaemia. Thus the prevalence of dyslipidaemia is much lower when compared with dysglycaemia in this rural population Our study (see Table 6) found that there was significant presence of poor blood glucose control, which rose significantly with age after 54 years, and its presence was equal in males and females.…”
Section: Discussionmentioning
confidence: 95%
“…38,39 In Nairobi, Kenya's capital city, a crosssectional survey across five socioeconomic classes reported a mean prevalence of metabolic syndrome of 35% (40% in women compared with 29% in men). 40 An autopsy study of the cardiovascular disease causes of death by the University of Nairobi reported a prevalence of 13% with the common conditions being myocardial infarction, cardiomyopathy, subarachnoid haemorrhage, pulmonary thromboembolism, ruptured aortic aneurysm and hypertensive heart disease. 41 The University of Nairobi laboratory, though a national referral hospital, still serves many Nairobi urban residents who are not national referrals.…”
Section: Discussionmentioning
confidence: 99%